The Role of Fiqh Teachers in Increasing Students' Awareness of the Benefits of Duha Prayer at MTs Al-Islahiyah Binjai - Ramadhan, Amalia; Hemawati, Hemawati; Pohan, Indra Satia (Jurnal Riset Ilmu Pendidikan, 2024)
The aim of this research is to determine the role of Fiqh teachers in making students aware of the benefits of Dhuha prayer at MTS Al-Islahiyah Binjai. Duha prayer has significant spiritual and social value in the daily lives of Muslims. This research was conducted using a qualitative approach with data collection techniques through observation, interviews and document analysis. The research results show that the role of Fiqh teachers is very important in increasing students' understanding of the benefits of the Dhuha prayer and encouraging them to do it regularly. The fiqh teacher acts as a helper, motivation and role model for students in performing the Dhuha prayer. The implications of this research highlight the need for an active role for Fiqh teachers in strengthening students' spiritual awareness of sunnah worship such as the Duha prayer as part of Islamic education at MTs Al-Islahiyah Binjai. In conclusion, collaboration between Fiqh teachers and students can improve understanding and practice of the Duha prayer, which ultimately has a positive impact on the formation of students' character and spirituality in Islamic educational institutions.